2007
DOI: 10.2113/gssajg.110.2-3.261
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Petroleum System Evolution of the southern Orange Basin, South Africa

Abstract: An integrated approach to investigate the petroleum system of the southern Orange Basin, South Africa reveals that the principal controls on hydrocarbon generation and leakage are spatial and temporal variations in post-rift overburden deposition. The model predicts present day gas seepage at the sea floor and this is calibrated against observed seepage events. D basin modelling of an east-west trending transect across the Orange Basin passive margin was undertaken accounting for variations in stratigraphy, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 30 publications
1
41
0
Order By: Relevance
“…A petroleum system modelling approach has been applied in various research studies (e.g. Burrus et al, 1991;Johannesen et al, 2002;Kubala et al, 2003;Paton et al 2007). Where sufficient data are available, thermal and petroleum systems models are useful in predicting the hydrocarbon potential of a basin.…”
Section: Introductionmentioning
confidence: 99%
“…A petroleum system modelling approach has been applied in various research studies (e.g. Burrus et al, 1991;Johannesen et al, 2002;Kubala et al, 2003;Paton et al 2007). Where sufficient data are available, thermal and petroleum systems models are useful in predicting the hydrocarbon potential of a basin.…”
Section: Introductionmentioning
confidence: 99%
“…(Light et al, 1993, 84 Muntingh & Brown, 1993, Paton et al, 2007, 2008, Hirsch et al, 2010. basin is extensive, though limited to the shelf margin, and has been used by previous studies (e.g.…”
mentioning
confidence: 99%
“…However, while a change in sediment supply could have surely played a role in shaping the overall subsidence history of the two basins, it is also possible that other processes might have come into play as well. In this regard, seismic profiles across the Orange Basin show several unconformities that are partially interpreted as erosional truncation horizons (Brown et al 1995;Hirsch et al, 2010;Kuhlmann, et al 2010;Paton et al, 2007). In addition, Hirsch et al (2010) evaluated that the best fit between modeled and observed vitrinite reflectance data can be achieved only by considering an erosion of about 1,000 m. Furthermore, erosional events are also in agreement with investigations onshore South Africa by Braun et al (2014).…”
Section: Discussionmentioning
confidence: 99%